The Influence of Person Job Fit and Organizational Culture on Employee Performance Through Job Satisfaction Intervening Variables at PT. Indo Dharma Transport Banjarmasin - M. Rio Mursid Wijaya; Fanlia Prima Jaya (Hut Publication Business and Management, 2021)
This research was conducted to find out the influence between Person Job Fit, Organizational Culture, on Employee Performance through intervening variables of Job Satisfaction in PT. Indo Dharma Transport Banjarmasin. The population of this research is as many as 24 employees of PT. Indo Dharma Transport Banjarmasin, to determine the sample, this study uses census techniques (saturated samples). The questionnaire was distributed to all 24 respondents. The data was analyzed using SPSS Software Version 25 and Multiple Linear Regression. The results showed person job fit and organizational culture towards employee performance through intervening variables job satisfaction has a significant effect.